Architecture, Environment, History: Questions and Consequences. Issue 2 (4th May 2018) - Barber, Daniel A.; Stickells, Lee; Ryan, Daniel J.; Koehler, Maren; Leach, Andrew; Goad, Philip; van der Plaat, Deborah; Keys, Cathy; Karim, Farhan; Taylor, William M.
Abstract : There is increasing interest among architectural historians in addressing environmental concerns on both historical and theoretical terms. Simultaneously, other fields have been looking to architectural scholarship to understand the historical relationship between the built and the natural environment. For architectural historians, and others, this has also involved correlating the shifting discourse on environment with a history of architectural transformations and disciplinary expansions. These engagements have made clear that the environmental history of architecture does not simply add more objects to the historical database, but also changes the terms of historical analysis, as new matters of concern and new conceptual frameworks come to the fore. This paper gathers together a dialogic set of projections from scholars responding to the question of how we might newly understand the historical relationship between the built and the natural environment, and the opportunities and challenges this new phase presents to scholars, design researchers, and architects.